Cytotypic variation in Phlox pilosa ssp. pilosa (Polemoniaceae) at the western edge of its range in the central United States - Worcester, Lindsey; Mayfield, Mark H.; Ferguson, Carolyn J. (My University, 2013)
Polyploidy occurs frequently in plants, and some species exhibit intraspecific variation in ploidy level, or cytotypic variation. This study investigated cytotypic variation in Phlox pilosa L. ssp. pilosa (Polemoniaceae) along the western edge of its range from north central Texas to southeastern Kansas. Flow cytometry was used to assess genome size for individuals from 46 populations, and meiosis was observed for several populations using compound light microscopy to enable linkage of flow cytometry data with chromosome number. Results demonstrate that P. pilosa ssp. pilosa occurs as diploid and tetraploid populations in the region, with tetraploids generally occurring to the west of diploid populations. Three populations exhibited genome size values that were higher than expected for tetraploids, possibly due to presence of B chromosomes. This work contributes to an improved understanding of polyploidy in the genus Phlox.
Keywords: Autopolyploidy; Chromosome count; Cytotype; Flow cytometry; Phlox; Polemoniaceae; Polyploidy